Distinctive Nested Glomoid Neoplasm: Clinicopathologic Analysis of 20 Cases of a Mesenchymal Neoplasm With Frequent GLI1 Alterations and Indolent Behavior. (24th January 2023) - Papke, David J.; Dickson, Brendan C.; Oliveira, Andre M.; Sholl, Lynette M.; Fletcher, Christopher D.M.
Abstract : Recently, it has been recognized that a subset of primary soft tissue neoplasms with GLI1 gene alterations exhibit nested architecture and can mimic glomus tumors or well-differentiated neuroendocrine tumors. Here, we report a series of 20 such neoplasms, which we have provisionally termed "distinctive nested glomoid neoplasm." Eleven patients (55%) were female and 9 were male. The median age at presentation was 41.5 years (range: congenital to 74 y). The anatomic distribution was wide, with body sites including the trunk (7 tumors), lower extremity (5), tongue (4), upper extremity (3), and neck (1). Excluding tumors of the tongue, 10 tumors (62%) arose in deep soft tissue and 6 (38%) arose primarily in the subcutis. Tumor size ranged from 0.9 to 11.1 cm (median: 3 cm). Distinctive nested glomoid neoplasms are composed of nests of round-to-ovoid cells with scant, palely eosinophilic cytoplasm and monomorphic nuclei with vesicular chromatin and small nucleoli. The nests are invested by prominent capillary networks, and they are situated within large lobules separated by irregular, thick fibrous septa. Among 18 tumors for which adjacent non-neoplastic tissue could be assessed, perivascular proliferation of tumor cells was identified in 16 tumors (89%). Microcystic architecture was present at least focally in 8 tumors (40%), and myxoid stroma was identified at least focally in 5 (25%). Seven tumors (35%) showed clear cell features. By immunohistochemistry, some tumors expressed MDM2 (7/15; 47%), S100 (5 of 19; 26%), STAT6 (2 of 5; 20%), and AE1/AE3 (1/5; 20%). Tumors rarely expressed pan-keratin (1/10; 10%) or CAM5.2 (1/10), and all tumors were negative for β-catenin (12 tumors), chromogranin (12), synaptophysin (11), epithelial membrane antigen (10), desmin (10), smooth muscle actin (9), INSM1 (7), and CD34 (6). GLI1 break-apart fluorescence in situ hybridization was performed on 7 tumors, and next-generation sequencing was performed on 15 tumors (10 DNA sequencing only, 1 RNA sequencing only, 4 both DNA and RNA sequencing). Sixteen tumors, including all 15 tested by next-generation sequencing and an additional case tested by fluorescence in situ hybridization only, were found to harbor GLI1 gene alterations: 10 harbored GLI1 gene rearrangements (3 ACTB :: GLI1, 2 PTCH1 :: GLI1, 1 HNRNPA1 :: GLI1, 1 NEAT1 :: GLI1, 1 TXNIP :: GLI1, 2 undetermined fusion partners), and 6 harbored GLI1 amplification. Clinical follow-up was available for 10 patients (50%; range: 3 mo to 10 y; median: 6.4 y), including 8 with >1 year of follow-up. Three patients (30%) experienced local recurrence (at intervals of 3 mo to 10 y). None developed distant metastases or died of disease as yet. Overall, our findings support the notion that a subset of GLI1 -altered soft tissue neoplasms are indolent, morphologically distinctive nested glomoid neoplasms that should not be classified as sarcomas.